Bearing Technology - Darji, Pranav H. (IntechOpen, 2017)
In the twenty-first century, bearings are expected to perform better in the form of various operating conditions, that is from low speed to extremely high speed and from low load to huge load applications. The expectations from the field of bearing technology are great. During the recent years, we have been witnessing the development of a new generation of mechanical systems that are highly miniaturized and very sophisticated, yet extremely robust. Technological progress creates increasingly arduous conditions for rolling mechanisms.